Online Test of Mathematics Learning for Fourth Grade Elementary School - Sabila, Sakin; Suarjana, I Made; Sumantri, Made (Jurnal Ilmiah Sekolah Dasar, 2021)
The current problem is teachers have difficulty in checking students’ work, this is caused all learning processes are carried out using mobile phone media. In addition, in the learning process during the Covid-19 period, teachers evaluate or provide other tasks only via WhatsApp. This study aims to create an online test of mathematics learning for fourth grade elementary school. The type of research used in this research was research and development. The model used in this study was using the ADDIE model. The research subjects were 2 experts in the field of learning mathematics and the trials test was conducted on 28 students in elementary school. The method used to collect data in this study used interviews and online tests. The data analysis techniques used were validity, reliability, discriminating power, level of difficulty, quality of distractors, practitioner responses and student responses. Instruments that have been designed to collect data are then tested first in order to find out the validity of the instrument. The result of the research was the analysis of the content validity test and the items were at very high criteria. The results of the reliability test, the instrument tested has a very high consistency. In the analysis of practitioner responses and student responses, the category was very good. So, the online test instrument for learning mathematics for fourth grade elementary school students was valid and feasible to be used as an instrument for assessing student learning outcomes. The implication of this research was the developed online test instrument can be used by teachers to measure students’ understanding during the learning process.